2020
DOI: 10.29215/pecen.v4i0.1327
|View full text |Cite
|
Sign up to set email alerts
|

Predation of the lizard <em>Tropidurus hispidus</em> (Squamata, Tropiduridae) by the vine snake <em>Oxybelis aeneus</em> (Serpentes: Colubridae) in the Caatinga, northeastern Brazil

Abstract: <p>A predação é um fator ecológico que regula a vida dos lagartos, entretanto, sua visualização na natureza é esporádica. Quando os predadores são serpentes crípticas, temos registros ainda mais escassos. Aqui nós apresentamos a predação de <em>Tropidurus hispidus</em> (Spix, 1825) pela serpente bicuda <em>Oxybelis aeneus</em> (Wagler <em>in</em> Spix, 1824). Alguns estudos já identificaram lagartos do gênero <em>Tropidurus</em> Wied-Neuwied, 1824 como pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Se ha mencionado que pequeñas lagartijas diurnas de condiciones ectotérmicas, constituyen un elemento básico en la dieta de todas las especies del género Oxybelis (Santana & Teixeira, 2020;Auguste et al, 2021;Campos et al, 2022;da Costa et al, 2022), incluso en O. aeneus se ha demostrado que es un depredador especialista en lagartijas (Mesquita et al, 2011). Cabe destacar la importancia ecológica de las especies del género Anolis como indicadores del estado del hábitat (Rengifo et al, 2019).…”
Section: Hernández-hernández Et Al-depredación De Anolis Rodrigueziiunclassified
“…Se ha mencionado que pequeñas lagartijas diurnas de condiciones ectotérmicas, constituyen un elemento básico en la dieta de todas las especies del género Oxybelis (Santana & Teixeira, 2020;Auguste et al, 2021;Campos et al, 2022;da Costa et al, 2022), incluso en O. aeneus se ha demostrado que es un depredador especialista en lagartijas (Mesquita et al, 2011). Cabe destacar la importancia ecológica de las especies del género Anolis como indicadores del estado del hábitat (Rengifo et al, 2019).…”
Section: Hernández-hernández Et Al-depredación De Anolis Rodrigueziiunclassified
“…Lucas Rafael Uchôa, Claylton de Abreu Costa, Sâmia Caroline Melo Araújo, Carina Uchôa Barbosa, Marta Angélica Pereira, Etielle Barroso de Andrade Biol Colomb, 28(1) 173 -177 Enero -Abril 2023 Information on diet is of great importance to understand the interaction of species with their environment and with other coexisting species, besides to understand how the eating habits are related to ecological and phylogenetic factors (França et al, 2008;Bellini et al, 2015). Ecological studies with snakes are scarce due to their cryptic habits, which means that information about diet and trophic ecology is, in most cases, obtained from specimens deposited in scientific collections (Bernarde, 2012;Dias-Silva et al, 2021) or through occasional records (Santana and Teixeira, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the position in which both prey items were found in the snake stomachs and based on the state of almost complete digestion of their heads, it can be concluded that they were ingested first by the head, which is a well-documented strategy in records of predation events by snakes on lizards (Almeida et al 2009, Menezes et al 2013, Maia-Carneiro et al 2016, Mikalauskas et al 2017, Sousa et al 2020, Santana & Teixeira 2020, Silva et al 2021. In fact, according to Greene (1976), this facilitates swallowing by reducing the resistance caused by the surface of the prey.…”
mentioning
confidence: 99%